2020
DOI: 10.1001/jamanetworkopen.2020.11809
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Progression-Free Survival Rate at 6 Months and Objective Response for Estimating Overall Survival in Immune Checkpoint Inhibitor Trials

Abstract: Key Points Question Can surrogate end points, such as progression-free survival, be used to estimate overall survival in immunotherapy trials? Findings This systematic review and meta-analysis using data from 60 published immunotherapy randomized clinical trials in advanced solid cancers found that 6-month progression-free survival in the immunotherapy arm estimated 12-month overall survival well using a statistical model that accounts for tumor type. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…This is a frequently reported statistic for many early phase oncology trials (Phase 1 and 2) that involve relatively small numbers of patients. It is also a landmark outcome in systematic reviews and metaanalysis of oncology clinical trials 39 , and used to guide the design of larger trials. A challenge in the analysis of such data is that, when too few events have occurred, nonparametric numeric confidence estimates return non-informative values (usually reported as a value "not reached" or "indeterminate" 27 as illustrated for two different scenarios in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is a frequently reported statistic for many early phase oncology trials (Phase 1 and 2) that involve relatively small numbers of patients. It is also a landmark outcome in systematic reviews and metaanalysis of oncology clinical trials 39 , and used to guide the design of larger trials. A challenge in the analysis of such data is that, when too few events have occurred, nonparametric numeric confidence estimates return non-informative values (usually reported as a value "not reached" or "indeterminate" 27 as illustrated for two different scenarios in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis of 60 published immunotherapy randomized clinical trials suggested that ORR could be a meager surrogate of response to evaluate the efficacy of IO, and the use of PFS as a surrogate of OS is still indeterminate [ 44 ]. Another meta-analysis of 12 randomized clinical trials did not find a significant positive correlation between the OS and PFS hazard estimates, suggesting that PFS assessment is not sufficient to capture the benefit of PD-1-inhibitors in patients with solid tumors [ 42 ].…”
Section: Challenges and Opportunities In Io Drugs Developmentmentioning
confidence: 99%
“…The increasing efficacy of immunotherapy with immune checkpoint inhibitors (ICIs) has deeply changed life expectancy for different types of fatal cancer: melanoma, lung cancer, renal carcinoma, advanced squamous cell carcinoma of the head and neck or skin districts, some colorectal cancers, and refractory lymphomas (1)(2)(3)(4)(5). At the same time, it is widely recognized that the therapeutic indication of ICI cannot be extended to all subtypes of tumor histology since it has been observed that majority of patients are not responsive (6).…”
Section: Introductionmentioning
confidence: 99%